2018
DOI: 10.1038/mi.2017.46
|View full text |Cite|
|
Sign up to set email alerts
|

Airway T cells protect against RSV infection in the absence of antibody

Abstract: Tissue resident memory T cells (Trm) act as sentinels and early responders to infection. RSV specific Trm have been detected in the lungs after human RSV infection, but whether they play a protective role is unknown. To dissect the protective function of Trm, BALB/c mice were infected with RSV; infected mice developed antigen specific CD8 + Trm (CD103 + /CD69 + ) in the lungs and airways.Intranasally transferring cells from the airways of previously infected animals to naïve animals reduced weight loss on infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 38 publications
(21 reference statements)
2
87
0
1
Order By: Relevance
“…As described in other infection models, RSV infection induces the generation of antigenspecific T RM expressing CD69 and CD103 within the lung parenchyma ( Fig. 1c) [38,56]. Additionally, RSV-specific T RM within the lung can also be generated by local immunization with RSV-derived antigens [12,57,58].…”
Section: Memory Cd8 T Cell Populations Following Rsv Infectionmentioning
confidence: 63%
See 2 more Smart Citations
“…As described in other infection models, RSV infection induces the generation of antigenspecific T RM expressing CD69 and CD103 within the lung parenchyma ( Fig. 1c) [38,56]. Additionally, RSV-specific T RM within the lung can also be generated by local immunization with RSV-derived antigens [12,57,58].…”
Section: Memory Cd8 T Cell Populations Following Rsv Infectionmentioning
confidence: 63%
“…Recent studies have demonstrated that T RM play a critical role in providing protection against secondary influenza virus infections [66][67][68]. Importantly, several reports have also supported a role for RSV-specific T RM in providing protection against RSV infection [12,[56][57][58]. Together, these studies establish that memory CD8 T cells provide protection against secondary RSV infection.…”
Section: Protection Against Secondary Infectionmentioning
confidence: 72%
See 1 more Smart Citation
“…[2][3][4] In addition, recent work suggests that tissue-resident B cells also form an important part of the adaptive immune defence in the lung. Many studies have focused on tissue-resident T cells (Trm cells) within lung tissues, and these adaptive immune cells have been shown to play an important part in host defence against a variety of pulmonary infections.…”
Section: Introductionmentioning
confidence: 99%
“…This RSV F subunit targeting vaccine has been demonstrated to elicit the expression of circulating neutralizing antibodies against RSV (Glenn et al, 2016). Toward the development of future adaptive immunity-inducing RSV vaccines, it has been demonstrated that the transfer of airway-resident T cells protect against RSV, where it has been suggested that, to lessen the burden of T cellemediated damage to airways, the induction of lung tissue T cells should be the focus of vaccine development (Kinnear et al, 2018).…”
Section: Respiratory Syncytial Virus Classification Epidemiology Immentioning
confidence: 99%